Minimal expression of myotonic dystrophy: a clinical and molecular analysis. Issue 11 (November 1992) - Reardon, W; Harley, H G; Brook, J D; Rundle, S A; Crow, S; Harper, P S; Shaw, D J
Abstract : A clinical and molecular study is reported of 83 patients considered to be minimally affected with myotonic dystrophy (DM). These had been identified in three ways: 60 subjects were identified on clinical grounds and were divided into those with and those without neuromuscular involvement (groups I and II); nine subjects were at high risk of carrying the DM gene but had a normal phenotype (group III); and 14 were parents of definitely affected patients where neither parent showed clinical abnormalities (group IV). PCR analysis of the CTG repeat in the DM gene showed a range of 70 to 230 repeats for the younger at risk patients in group III, while the asymptomatic gene carriers in group IV had 53 to 60 repeats. The sensitivity of diagnosis by EMG was found to be 39%. For ophthalmic signs this was 97.5%. This suggests that assignment on the basis of minimal clinical features carries a significant error. Molecular analysis, in conjunction with established clinical investigations, should prove valuable in the identification and exclusion of minimal myotonic dystrophy.